Crude glycerin in supplement to primiparous lactating cows grazing on tropical pasture: nutritional and productive characteristics - Santana Júnior,Hermógenes Almeida de (2013)
The objective of this study was to evaluate the nutritional and productive characteristics of primiparous lactating cows grazing on tropical pasture, using different levels of crude glycerin in the supplement. The experiment was conducted at Rancho Santana farm, located in Jequié city, Bahia, Brazil, in the period from December 21, 2010 to March 16, 2011. Ten ¾ Holstein × ¼ Dairy Gyr lactating primiparous cows, with 109±24 days of lactation and a mean age of 30±6 months and mean body weight of 426.2±68.29 kg were distributed into five treatments, using two simultaneous 5 × 5 latin squares. Treatments consisted of inclusion levels (0, 94, 191, 289, 389 g/kg dry matter basis) of crude glycerin in the supplement. Intake, digestibility, milk production and composition were measured. Results were statistically analyzed by analysis of variance and regression at 0.05 probability. For all consumption variables no significant differences were found between the levels of crude glycerin. Except for the digestibility of ether extract, all digestibility values were similar between treatments. The fat content and yield showed quadratic effect between treatments. No significant differences were observed for protein, lactose, total solids, nonfat dry extract, fat:protein ratio, milk urea nitrogen and somatic cell count between treatments. For primiparous lactating cows grazing on tropical pasture, up to 389 g of crude glycerin/kg of dietary supplement can be included without nutritional and productive interference.